2004
DOI: 10.1208/aapsj060317
|View full text |Cite
|
Sign up to set email alerts
|

Formulation design of double-layer in the outer shell of dry-coated tablet to modulate lag time and time-controlled dissolution function: Studies on micronized ethylcellulose for dosage form design (VII)

Abstract: The dry-coated tablet with optimal lag time was designed to simulate the dosing time of drug administration according to the physiological needs. Different compositions of ethylcellulose (EC) powder with a coarse particle (167.5 µm) and several fine particles (<6 µm), respectively, were mixed to formulate the whole layer of the outer shell of dry-coated tablets. The formulations containing different weight ratios of coarse/fine particles of EC powders or 167.5 µm EC powder/excipient in the upper layer of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Modifications of half of the coating formula were demonstrated to be a further means of modulating the lag phase. The obtained bipartite shells, however, possibly involved release mechanisms other than that observed when testing units coated with EC only (Lin et al, 2004b).…”
Section: Delivery Systems Based On Release-controlling Coatingsmentioning
confidence: 83%
“…Modifications of half of the coating formula were demonstrated to be a further means of modulating the lag phase. The obtained bipartite shells, however, possibly involved release mechanisms other than that observed when testing units coated with EC only (Lin et al, 2004b).…”
Section: Delivery Systems Based On Release-controlling Coatingsmentioning
confidence: 83%
“…The higher mucoadhesion of carbopol 934P microspheres may also be attributed to the higher molecular weight of carbopol than HPMC [29]. These polymers are often used as a rate-controlling membrane to modulate the drug release from dosage forms with organic or aqueous coating techniques [30][31][32][33]. The principle of gelation or crosslinking of sodium alginate with aluminium chloride is based on the formation of a tight junction between the residues of guluronic acid.…”
Section: In Vitro Dissolutionmentioning
confidence: 99%
“…The dry-coated tablet dosage form (i.e., the tablet-in-tablet design) is a time-and rate-controlled drug delivery device, which consists of a core tablet and an outer layer that is considerably thicker than typical tablet coats, and which completely surrounds the core (inner) tablet. Previous studies have reported that various drug release mechanisms have been realized by incorporating a range of excipients into the outer shell of the dry-coated tablet (Lin et al, 2004). The dry-coated tablet is typically manufactured utilizing a two-step compaction process where the inner core precedes the outer coating compaction in a specialized tablet press.…”
Section: Introductionmentioning
confidence: 99%